Tiered maize and wheat nutrient removal coefficients estimated from available data - C. I. Ludemann; R. Hijbeek; M. P. van Loon; T. S. Murrell; A. Dobermann; M. K. van Ittersum (Nutrient Cycling in Agroecosystems, 2025)
Estimates of cropland nutrient budgets at national to global scale generally rely on regional or global mean coefficients for quantifying nutrients removed in crop yield and by-products. Use of such mean values masks the variability in these coefficients. Using maize and wheat as examples, we assessed variation in nutrient removal coefficients, namely harvest index (HI), nitrogen (N), phosphorus (P) and potassium (K) concentrations of crop products (Grain N, Grain P and Grain K respectively) and N, P and K concentrations of crop residues (Residue N, Residue P, and Residue K respectively). Variation in these coefficients was assessed by three categories (Tiers) of estimation. Statistical (mixed-effects) and machine learning (random forest regression) models (Tier 3) were used to predict the coefficients using generally available predictor variables at a global level. Mean prediction accuracies (R 2 ) of the mixed-effects and random forest models were 0.32 for maize coefficients and 0.45 for wheat coefficients when based on a random sub-selection of mainly replicated field experiment data. When predictions were applied to on-farm data only, prediction accuracies were lower (mean R 2 values of 0.08 and 0.36 for maize and wheat respectively). Variation in, and dearth of on-farm data for the coefficients contributed to these poor prediction accuracies. Until the limitations of on-farm data are overcome, it is recommended to use Tier 2 (regional) coefficient estimates in country and global cropland nutrient balance and nutrient use efficiency estimates. Where Tier 2 values are not available, then global average (Tier 1) coefficients can be used.

Disparities in lung cancer screening utilization at two health systems in the Southeastern USA - Soumya J. Niranjan; Desiree Rivers; Rekha Ramachandran; JEdward Murrell; Kayleigh C. Curry; Mohammed Mubasher; Eric Flenaugh; Mark T. Dransfield; Sejong Bae; Isabel C. Scarinci (Cancer Causes & Control, 2025)

Everyday places to get away – Lessons learned from Covid-19 lockdowns - B. Gatersleben; E. White; K.J. Wyles; S.E. Golding; G. Murrell; C. Scarles; T. Xu; B.F.T. Brockett; C. Willis (Landscape and Urban Planning, 2024)

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

Contrasting trajectories of morphological diversification on continents and islands in the Afrotropical white‐eye radiation - Julia J. Day; Frederico C. Martins; Joseph A. Tobias; David J. Murrell (Journal of Biogeography, 2020)
Aim Morphological and lineage evolution are predicted to follow different patterns in island and mainland radiations. However, the extent to which these geographical contexts influence evolutionary trajectories remains poorly understood, in part because few studies have focused on species‐rich clades colonizing continents and archipelagos over comparable timeframes. Focusing on a diverse songbird clade radiating on the African continent and adjacent islands, we tested whether morphological evolution is best explained by adaptive or non‐adaptive processes, and whether mainland and island lineages evolved to occupy different regions or volumes of morphological space (morphospace). Location Palaeotropics, with a particular focus on the Afrotropical region. Taxon White‐eyes, Zosterops (Aves: Zosteropidae). Methods We generated principal component axes from novel trait data for 120 species and combined this information with a comprehensive dated phylogeny. We then analysed the dynamics of trait and lineage diversification using comparative evolutionary methods. Results An early burst and slowdown pattern of lineage accumulation is not mirrored by phenotypic evolution, which instead shows an apparent convergence on particular phenotypes. However, the overall signature of phenotypic convergence is strongly driven by mainland taxa, in which phenotypes appear to be highly constrained within elevational zones, while speciation events are often associated with phenotypic divergence from one body plan to the other after colonization of highland from lowland habitats, or vice versa. By contrast, island lineages have repeatedly explored novel areas of morphospace with patterns of phenotypic divergence generally not distinguishable from a random‐walk model. Main conclusions Diversification of Zosterops highlights contrasting evolutionary trends and dynamics for continental versus island species. We suggest the different trajectory of evolution in insular lineages arises from reduced species competition leading to an increase in ecological opportunity, thereby providing a release to phenotypic constraints experienced by continental taxa.

Seasonal Oxygen Dynamics in a Warm Temperate Estuary: Effects of Hydrologic Variability on Measurements of Primary Production, Respiration, and Net Metabolism - Michael C. Murrell; Jane M. Caffrey; Dragoslav T. Marcovich; Marcus W. Beck; Brandon M. Jarvis; James D. Hagy (Estuaries and Coasts, 2018)

Isolation of isoprene degrading bacteria from soils, development of isoA gene probes and identification of the active isoprene‐degrading soil community using DNA‐stable isotope probing - Myriam El Khawand; Andrew T. Crombie; Antonia Johnston; Dmitrii V. Vavlline; Joseph C. McAuliffe; Jacob A. Latone; Yuliya A. Primak; Sang‐Kyu Lee; Gregg M. Whited; Terry J. McGenity; J. Colin Murrell (Environmental Microbiology, 2016)
Summary Emissions of biogenic volatile organic compounds (bVOCs), are an important element in the global carbon cycle, accounting for a significant proportion of fixed carbon. They contribute directly and indirectly to global warming and climate change and have a major effect on atmospheric chemistry. Plants emit isoprene to the atmosphere in similar quantities to emissions of methane from all sources and each accounts for approximately one third of total VOCs. Although methanotrophs, capable of growth on methane, have been intensively studied, we know little of isoprene biodegradation. Here, we report the isolation of two isoprene‐degrading strains from the terrestrial environment and describe the design and testing of polymerase chain reaction (PCR) primers targeting isoA , the gene encoding the active‐site component of the conserved isoprene monooxygenase, which are capable of retrieving isoA sequences from isoprene‐enriched environmental samples. Stable isotope probing experiments, using biosynthesized 13 C‐labelled isoprene, identified the active isoprene‐degrading bacteria in soil. This study identifies novel isoprene‐degrading strains using both culture‐dependent and, for the first time, culture‐independent methods and provides the tools and foundations for continued investigation of the biogeography and molecular ecology of isoprene‐degrading bacteria.

Cell-free mitochondrial DNA in CSF is associated with early viral rebound, inflammation, and severity of neurocognitive deficits in HIV infection - Josué Pérez-Santiago; Rachel D. Schrier; Michelli F. de Oliveira; Sara Gianella; Susanna R. Var; Tyler R. C. Day; Miguel Ramirez-Gaona; Jesse D. Suben; Ben Murrell; Marta Massanella; Mariana Cherner; Davey M. Smith; et al. (Journal of NeuroVirology, 2016)

Regulation of plasmid‐encoded isoprene metabolism in R hodococcus , a representative of an important link in the global isoprene cycle - Andrew T. Crombie; Myriam El Khawand; Virgil A. Rhodius; Kevin A. Fengler; Michael C. Miller; Gregg M. Whited; Terry J. McGenity; J. Colin Murrell (Environmental Microbiology, 2015)
Summary Emissions of biogenic volatile organic compounds ( VOCs ) form an important part of the global carbon cycle, comprising a significant proportion of net ecosystem productivity. They impact atmospheric chemistry and contribute directly and indirectly to greenhouse gases. Isoprene, emitted largely from plants, comprises one third of total VOCs , yet in contrast to methane, which is released in similar quantities, we know little of its biodegradation. Here, we report the genome of an isoprene degrading isolate, R hodococcus sp. AD 45, and, using mutagenesis shows that a plasmid‐encoded soluble di‐iron centre isoprene monooxygenase ( IsoMO ) is essential for isoprene metabolism. Using RNA sequencing ( RNAseq ) to analyse cells exposed to isoprene or epoxyisoprene in a substrate‐switch time‐course experiment, we show that transcripts from 22 contiguous genes, including those encoding IsoMO , were highly upregulated, becoming among the most abundant in the cell and comprising over 25% of the entire transcriptome. Analysis of gene transcription in the wild type and an IsoMO ‐disrupted mutant strain showed that epoxyisoprene, or a subsequent product of isoprene metabolism, rather than isoprene itself, was the inducing molecule. We provide a foundation of molecular data for future research on the environmental biological consumption of this important, climate‐active compound.

Human cytomegalovirus: taking the strain - Gavin W. G. Wilkinson; Andrew J. Davison; Peter Tomasec; Ceri A. Fielding; Rebecca Aicheler; Isa Murrell; Sepher Seirafian; Edward C. Y. Wang; Michael Weekes; Paul J. Lehner; Gavin S. Wilkie; Richard J. Stanton (Medical Microbiology and Immunology, 2015)

Carbon Dynamics on the Louisiana Continental Shelf and Cross-Shelf Feeding of Hypoxia - Brian Fry; Dubravko Justić; Philip Riekenberg; Erick M. Swenson; R. Eugene Turner; Lixia Wang; Lora Pride; Nancy N. Rabalais; Janis C. Kurtz; John C. Lehrter; Michael C. Murrell; Elizabeth H. Shadwick; et al. (Estuaries and Coasts, 2015)

Erratum to: Seasonal and Inter-annual Patterns in Primary Production, Respiration, and Net Ecosystem Metabolism in Three Estuaries in the Northeast Gulf of Mexico - Jane M. Caffrey; Michael C. Murrell; Kendra S. Amacker; Jennifer W. Harper; Scott Phipps; Mark S. Woodrey (Estuaries and Coasts, 2014)

Seasonal and Inter-annual Patterns in Primary Production, Respiration, and Net Ecosystem Metabolism in Three Estuaries in the Northeast Gulf of Mexico - Jane M. Caffrey; Michael C. Murrell; Kendra S. Amacker; Jennifer W. Harper; Scott Phipps; Mark S. Woodrey (Estuaries and Coasts, 2014)

Methanobactin and MmoD work in concert to act as the ‘copper‐switch’ in methanotrophs - Jeremy D. Semrau; Sheeja Jagadevan; Alan A. DiSpirito; Ashraf Khalifa; Julie Scanlan; Brandt H. Bergman; Brittani C. Freemeier; Bipin S. Baral; Nathan L. Bandow; Alexey Vorobev; Daniel H. Haft; Stéphane Vuilleumier; et al. (Environmental Microbiology, 2013)
Summary Biological oxidation of methane to methanol by aerobic bacteria is catalysed by two different enzymes, the cytoplasmic or soluble methane monooxygenase ( sMMO ) and the membrane‐bound or particulate methane monooxygenase ( pMMO ). Expression of MMOs is controlled by a ‘copper‐switch’, i.e. sMMO is only expressed at very low copper : biomass ratios, while pMMO expression increases as this ratio increases. Methanotrophs synthesize a chalkophore, methanobactin, for the binding and import of copper. Previous work suggested that methanobactin was formed from a polypeptide precursor. Here we report that deletion of the gene suspected to encode for this precursor, mbnA , in M ethylosinus trichosporium OB3 b, abolishes methanobactin production. Further, gene expression assays indicate that methanobactin, together with another polypeptide of previously unknown function, MmoD , play key roles in regulating expression of MMOs . Based on these data, we propose a general model explaining how expression of the MMO operons is regulated by copper, methanobactin and MmoD . The basis of the ‘copper‐switch’ is MmoD , and methanobactin amplifies the magnitude of the switch. Bioinformatic analysis of bacterial genomes indicates that the production of methanobactin‐like compounds is not confined to methanotrophs, suggesting that its use as a metal‐binding agent and/or role in gene regulation may be widespread in nature.

The memory of spatial patterns: changes in local abundance and aggregation in a tropical forest - Anton J. Flügge; Sofia C. Olhede; David J. Murrell (Ecology, 2012)
The current spatial pattern of a population is the result of previous individual birth, death, and dispersal events. We present a simple model followed by a comparative analysis for a species‐rich plant community to show how the current spatial aggregation of a population may hold information about recent population dynamics. Previous research has shown how locally restricted seed dispersal often leads to stronger aggregation in less abundant populations than it does in more abundant populations. In contrast, little is known about how changes in the local abundance of a species may affect the spatial distribution of individuals. If the level of aggregation within a species depends to some extent on the abundance of the species, then changes in abundance should lead to subsequent changes in aggregation. However, an overall change of spatial pattern relies on many individual birth and death events, and a surplus of deaths or births may have short‐term effects on aggregation that are opposite to the long‐term change predicted by the change in abundance. The change in aggregation may therefore lag behind the change in abundance, and consequently, the current aggregation may hold information about recent population dynamics. Using an individual‐based simulation model with local dispersal and density‐dependent competition, we show that, on average, recently growing populations should be more aggregated than shrinking populations of the same current local abundance. We tested this hypothesis using spatial data on individuals from a long‐term tropical rain forest plot, and find support for this relationship in canopy trees, but not in understory and shrub species. On this basis we argue that current spatial aggregation is an important characteristic that contains information on recent changes in local abundance, and may be applied to taxonomic groups where dispersal is limited and within‐species aggregation is observed.

Carbon dynamics and community production in the Mississippi River plume - Xianghui Guo; Wei-Jun Cai; Wei-Jen Huang; Yongchen Wang; Feizhou Chen; Michael C. Murrell; Steven E. Lohrenz; Li-Qing Jiang; Minhan Dai; Justin Hartmann; Qi Lin; Randy Culp (Limnology and Oceanography, 2012)
Dissolved inorganic carbon (DIC), total alkalinity (TAlk), pH, and dissolved oxygen (DO) were determined in the Mississippi River plume during five cruises conducted in the spring, summer, and fall. In contrast to many other large rivers, both DIC and TAlk were higher in river water than in seawater. Substantial losses of DIC, relative to TAlk, occurred within the plume, particularly at intermediate salinities. DIC removal was accompanied by high DO, high pH, and nutrient depletion, and was attributed to high phytoplankton production. As a result, the carbonate saturation in the plume became much higher than in ocean and river waters. A mixing model was used to determine DIC removal. We provide evidence that the use of a two—end‐member (river and ocean) mixing model was valid during late summer and fall (low discharge period). However, for other periods we used salinity and TAlk to delineate a mixing model that included two river end members and an ocean end member. Net community production rates in the plume, estimated using a box model, peaked in the summer and were among the highest reported to date for large river plumes. In the summer and fall, biological production in the river plume consumed a majority of the available nutrients, whereas during the spring only a small fraction of the available nutrients were consumed in the plume. Biological production was the dominant process influencing pH and carbonate saturation state along the river—ocean gradient, whereas physicochemical dynamics of mixing played an important role in controlling the TAlk and DIC distributions of this large river plume.

Sediment and Lower Water Column Oxygen Consumption in the Seasonally Hypoxic Region of the Louisiana Continental Shelf - Michael C. Murrell; John C. Lehrter (Estuaries and Coasts, 2011)

Marine brevetoxin induces IgE-independent mast cell activation - Susana C. Hilderbrand; Rachel N. Murrell; James E. Gibson; Jared M. Brown (Archives of Toxicology, 2011)

Cardiovascular function and the veteran athlete - M. Wilson; R. O’Hanlon; S. Basavarajaiah; K. George; D. Green; P. Ainslie; S. Sharma; S. Prasad; C. Murrell; D. Thijssen; A. Nevill; G. Whyte (European Journal of Applied Physiology, 2010)

Effects of intermittent hypoxia on SaO2, cerebral and muscle oxygenation during maximal exercise in athletes with exercise-induced hypoxemia - Helen C. Marshall; Michael J. Hamlin; John Hellemans; Carissa Murrell; Nik Beattie; Ien Hellemans; Tracy Perry; Aimee Burns; Philip N. Ainslie (European Journal of Applied Physiology, 2008)

Hypoxia in the northern Gulf of Mexico: Does the science support the Plan to Reduce, Mitigate, and Control Hypoxia? - N. N. Rabalais; R. E. Turner; B. K Sen Gupta; D. F. Boesch; P. Chapman; M. C. Murrell (Estuaries and Coasts, 2007)

Phytoplankton production and nutrient distributions in a subtropical estuary: Importance of freshwater flow - Michael C. Murrell; James D. Hagy; Emile M. Lores; Richard M. Greene (Estuaries and Coasts, 2007)

Effects of Hurricane Ivan on water quality in Pensacola Bay, Florida - James D. Hagy; John C. Lehrter; Michael C. Murrell (Estuaries and Coasts, 2006)

Spontaneous recovery of injured Achilles tendon in inducible nitric oxide synthase gene knockout mice - W. Xia; Y. Wang; R. C. Appleyard; G. A. Smythe; G. A. C. Murrell (Inflammation Research, 2006)

Bacterial diversity in the bacterioneuston (sea surface microlayer): the bacterioneuston through the looking glass - Mark P. Franklin; Ian R. McDonald; David G. Bourne; Nicholas J. P. Owens; Robert C. Upstill‐Goddard; J. Colin Murrell (Environmental Microbiology, 2005)
Summary The bacterioneuston is defined as the community of bacteria present within the neuston or sea surface microlayer. Bacteria within this layer were sampled using a membrane filter technique and bacterial diversity was compared with that in the underlying pelagic coastal seawater using molecular ecological techniques. 16S rRNA gene libraries of ≈ 500 clones were constructed from both bacterioneuston and the pelagic water samples and representative clones from each library were sequenced for comparison of bacterial diversity. The bacterioneuston was found to have a significantly lower bacterial diversity than the pelagic seawater, with only nine clone types (ecotaxa) as opposed to 46 ecotaxa in the pelagic seawater library. Surprisingly, the bacterioneuston clone library was dominated by 16S rRNA gene sequences affiliated to two groups of organisms, Vibrio spp. which accounted for over 68% of clones and Pseudoalteromonas spp. accounting for 21% of the library. The dominance of these two 16S rRNA gene sequence types within the bacterioneuston clone library was confirmed in a subsequent gene probing experiment. 16S rRNA gene probes specific for these groups of bacteria were designed and used to probe new libraries of 1000 clones from both the bacterioneuston and pelagic seawater DNA samples. This revealed that 57% of clones from the bacterioneuston library hybridized to a Vibrio sp.‐specific 16S rRNA gene probe and 32% hybridized to a Pseudoalteromonas sp.‐specific 16S rRNA gene probe. In contrast, the pelagic seawater library resulted in only 13% and 8% of 16S rRNA gene clones hybridizing to the Vibrio sp. and Pseudoalteromonas sp. probes respectively. Results from this study suggest that the bacterioneuston contains a distinct population of bacteria and warrants further detailed study at the molecular level.

Synonymy of Boophilus Curtice, 1891 with Rhipicephalus Koch, 1844 (Acari: Ixodidae) - Anna Murrell; Stephen C. Barker (Systematic Parasitology, 2003)

Phylogeny of the lice (Insecta, Phthiraptera) inferred from small subunit rRNA - Stephen C. Barker; Michael Whiting; Kevin P. Johnson; Anna Murrell (Zoologica Scripta, 2003)
There has been much argument about the phylogenetic relationships of the four suborders of lice (Insecta: Phthiraptera). Lyal's study of the morphology of lice indicated that chewing/biting lice (Mallophaga) are paraphyletic with respect to sucking lice (Anoplura). To test this hypothesis we inferred the phylogeny of 33 species of lice from small subunit (SSU) rRNA sequences (18S rRNA). Liposcelis sp. from the Liposcelididae (Psocoptera) was used for outgroup reference. Phylogenetic relationships among the four suborders of lice inferred from these sequences were the same as those inferred from morphology. The Amblycera is apparently the sister‐group to all other lice whereas the Rhynchophthirina is apparently sister to the Anoplura; these two suborders are sister to the Ischnocera, i.e. (Amblycera (Ischnocera (Anoplura, Rhynchophthirina))). Thus, the Mallophaga (Amblycera, Ischnocera, Rhynchophthirina) is apparently paraphyletic with respect to the Anoplura. Our analyses also provide evidence that: (i) each of the three suborders of lice that are well represented in our study (the Amblycera, Ischnocera, and Anoplura) are monophyletic; (ii) the Boopiidae is monophyletic; (iii) the genera Heterodoxus and Latumcephalum (Boopiidae) are more closely related to one another than either is to the genus Boopia (also Boopiidae); (iv) the Ricinidae and Laemobothridae may be sister‐taxa; (v) the Philopteridae may be paraphyletic with respect to the Trichodectidae; (vi) the genera Pediculus and Pthirus are more closely related to each other than either is to the genus Pedicinus ; and (vii) in contrast to published data for mitochondrial genes, the rates of nucleotide substitution in the SSU rRNA of lice are not higher than those of other insects, nor do substitution rates in the suborders differ substantially from one another.

Effects of native forest regeneration practices on genetic diversity in Eucalyptus consideniana - Jeffrey C. Glaubitz; Jan C. Murrell; Gavin F. Moran (Theoretical and Applied Genetics, 2003)

Growth of sulfate-reducing bacteria and methanogenic archaea with methylated sulfur compounds: a commentary on the thermodynamic aspects - Johannes C. M. Scholten; J. Colin Murrell; Donovan P. Kelly (Archives of Microbiology, 2003)

Growth of sulfate-reducing bacteria and methanogenic archaea with methylated sulfur compounds: a commentary on the thermodynamic aspects - Johannes C. M. Scholten; J. Colin Murrell; Donovan P. Kelly (Archives of Microbiology, 2003)

Phylogeny, Evolution and Historical Zoogeography of Ticks: A Review of Recent Progress - Stephen C. Barker; Anna Murrell (Experimental and Applied Acarology, 2002)

A review of bacterial methyl halide degradation: biochemistry, genetics and molecular ecology - I. R. McDonald; K. L. Warner; C. McAnulla; C. A. Woodall; R. S. Oremland; J. C. Murrell (Environmental Microbiology, 2002)
Summary Methyl halide‐degrading bacteria are a diverse group of organisms that are found in both terrestrial and marine environments. They potentially play an important role in mitigating ozone depletion resulting from methyl chloride and methyl bromide emissions. The first step in the pathway(s) of methyl halide degradation involves a methyltransferase and, recently, the presence of this pathway has been studied in a number of bacteria. This paper reviews the biochemistry and genetics of methyl halide utilization in the aerobic bacteria Methylobacterium chloromethanicum CM4 T , Hyphomicrobium chloromethanicum CM2 T , Aminobacter strain IMB‐1 and Aminobacter strain CC495. These bacteria are able to use methyl halides as a sole source of carbon and energy, are all members of the α ‐Proteobacteria and were isolated from a variety of polluted and pristine terrestrial environments. An understanding of the genetics of these bacteria identified a unique gene ( cmuA ) involved in the degradation of methyl halides, which codes for a protein (CmuA) with unique methyltransferase and corrinoid functions. This unique functional gene, cmuA , is being used to develop molecular ecology techniques to examine the diversity and distribution of methyl halide‐utilizing bacteria in the environment and hopefully to understand their role in methyl halide degradation in different environments. These techniques will also enable the detection of potentially novel methyl halide‐degrading bacteria.

Microbial metabolism of methanesulfonic acid - D. P. Kelly; J. C. Murrell (Archives of Microbiology, 1999)

Desulfonation of propanesulfonic acid by Comamonas acidovorans strain P53: evidence for an alkanesulfonate sulfonatase and an atypical sulfite dehydrogenase - W. Reichenbecher; D. P. Kelly; J. C. Murrell (Archives of Microbiology, 1999)

Heterologous expression of soluble methane monooxygenase genes in methanotrophs containing only particulate methane monooxygenase - John S. Lloyd; Paolo De Marco; Howard Dalton; J. C. Murrell (Archives of Microbiology, 1999)

Bacterioplankton dynamics in northern San Francisco Bay: Role of particle association and seasonal freshwater flow - M. C. Murrell; J. T. Hollibaugh; M. W. Silver; P. S. Wong (Limnology and Oceanography, 1999)
Bacterioplankton abundance and metabolic characteristics were observed in northern San Francisco Bay, California, during spring and summer 1996 at three sites: Central Bay, Suisun Bay, and the Sacramento River. These sites spanned a salinity gradient from marine to freshwater, and sampling occurred during a period of seasonally declining river flow. The microbial measures included radio‐labeled amino acid uptake (L‐leucine, L‐proline, L‐serine), ectoenzyme activity (aminopeptidase and β‐D‐glucosidase), and bacterial abundance using 1‐µm filters to separate free from particle‐associated bacteria. A seasonal decline in all bacterial metabolic measures was observed at all stations, suggesting that a system‐wide variable may be important in controlling bacterial activity. One such variable is freshwater flow into the Bay (as a proxy for organic matter flux), which positively covaried with all metabolic measures. A sharp decline in particle‐associated bacteria was also observed in Suisun Bay and the Sacramento River between July and August. This decline may have been due to combined effects of declining nutritive value of the aging particles and increasing grazing pressure by benthic filter feeders. Aminopeptidase activity was positively related with increasing salinity, and β‐D‐glucosidase was negatively correlated with increasing salinity, indicating a gradient in the relative quality of organic matter from carbohydrate‐rich riverine to protein‐rich oceanic material. Overall, Suisun Bay had the highest mean proportion of particle‐associated bacteria (49%), followed by Sacramento River (36%) and Central Bay (11%). Particles were the sites of enhanced ectoenzyme activity but not amino acid incorporation. Bacteria may be actively dissolving the particulate organic matter, but their growth rates on particles are not significantly enhanced.

Analysis of 16S rRNA and methane monooxygenase gene sequences reveals a novel group of thermotolerant and thermophilic methanotrophs, Methylocaldum gen. nov. - Levente Bodrossy; E. M. Holmes; A. J. Holmes; Kornél L. Kovács; J. C. Murrell (Archives of Microbiology, 1997)

Mapping of quantitative trait loci influencing frost tolerance in Eucalyptus nitens - M. Byrne; J. C. Murrell; J. V. Owen; E. R. Williams; G. F. Moran (Theoretical and Applied Genetics, 1997)

Detection of methanogens and methanotrophs in natural environments - D.A. RITCHIE; C. EDWARDS; I. R. McDONALD; J. C. MURRELL (Global Change Biology, 1997)
The role of methane as a greenhouse gas and the contribution of bacteria to the production (methanogenesis) and destruction (methane oxidation) of methane is described. Using experimental approaches based on DNA sequences identifying either methanogen‐specific or methanotroph‐specific gene sequences methods were developed to broaden the detection and identification of methane metabolizing bacteria in natural environments. These methods were focused on blanket bog peat but are suitable for other environments. In addition to group specific 16S rRNA DNA sequences, specific functional gene probes based on methane coenzyme reductase sequences for methanogens and methane monooxygenase sequences for methanotrophs, were developed. These sequences were used in PCR‐based protocols to detect and amplify specific gene sequences from the total DNA isolated from transverse sections of blanket bog peat. This permitted the analysis of the vertical distribution of methanogen and methanotroph populations, discrimination between different sub‐sets of these populations, and the identification of novel organisms not previously detected by culture‐based methods.

Identification and mode of action of quantitative trait loci affecting seedling height and leaf area in Eucalyptus nitens - M. Byrne; J. C. Murrell; J. V. Owen; P. Kriedemann; E. R. Williams; G. F. Moran (Theoretical and Applied Genetics, 1997)

Methylosulfonomonas methylovora gen. nov., sp. nov., and Marinosulfonomonas methylotropha gen. nov., sp. nov.: novel methylotrophs able to grow on methanesulfonic acid - Andrew J. Holmes; D. P. Kelly; Simon C. Baker; A. S. Thompson; Paolo De Marco; Elizabeth M. Kenna; J. Colin Murrell (Archives of Microbiology, 1997)

Modulation of tendon healing by nitric oxide - G. A. C. Murrell; C. Szabo; J. A. Hannafin; Not Available Not Available; D. Jang; M. M. Dolan; X.-H. Deng; D. F. Murrell; R. F. Warren (Inflammation Research, 1997)

The methane monooxygenase gene cluster of Methylosinus trichosporium: cloning and sequencing of the mmoC gene - D. L. N. Cardy; V. Laidler; G. P. C. Salmond; J. C. Murrell (Archives of Microbiology, 1991)

Molecular analysis of methane monooxygenase from Methylococcus capsulatus (Bath) - Andrew C. Stainthorpe; J. Colin Murrell; George P. C. Salmond; Howard Dalton; Veronica Lees (Archives of Microbiology, 1989)